A comment on the protect–manage–then‐restore workflow. Issue 1 (5th April 2022) - Lortie, Christopher J.
Abstract : Decisions and judgment are complex processes. There is a dire need to redress, offset, and salvage function in most natural systems with the profound pressures exerted by global change. We must judge threats and decide between solutions. A recent perspective from a climate mediation perspective proposed a hierarchical approach to consider with respect to the implementation timing for interventions by restoration ecologists. The three steps in descending order of estimated returns included protect first, manage, then restore. This opinion discusses the value of the optimization, and concludes that the workflow is reasonable for many other global grand challenges in addition to restorations that potentially mitigate climate effects.